Single and double charmed meson production at the LHC - Maciula Rafal; Szczurek Antoni (EPJ Web of Conferences, 2014)
We discuss production of charmed mesons in proton-proton collisions at the LHC. The cross section for inclusive production of cc̄ pairs is calculated in the frame-work of the k⊥-factorization approach which effectively includes next-to-leading order corrections. Theoretical uncertainties of the model related to the choice of renormalization and factorization scales as well as due to the quark mass are discussed. Results of the k⊥-factorization approach are compared to NLO parton model predictions. The hadronization of charm quarks is included with the help of the Peterson fragmentation functions. Inclusive differential distributions in transverse momentum for several charmed mesons (D0, D±, Ds±) are calculated and compared to recent results of the ALICE, ATLAS and LHCb collaborations. Furthermore, we also discuss production of two pairs cc̄ of within a simple formalism of double-parton scattering (DPS). Surprisingly large cross sections, comparable to single-parton scattering (SPS) contribution, are predicted for LHC energies. We compare our predictions for double charm production (DD meson-meson pairs) with recent results of the LHCb collaboration for azimuthal angle ϕDD and rapidity distance between mesons YDD. Meson-meson kinematical correlations are also confronted with those related to the standard meson-antimeson measurements. Our calculations clearly confirm the dominance of DPS in the production of events with double charm, however some strength seems to be still lacking. Possible missing contribution within the framework of single-ladder-splitting DPS mechanism is also discussed.